1991
DOI: 10.3109/00016489109131431
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on the Visuo- and Vestibulo-ocular Reflexes of Elderly Patients with Vertigo

Abstract: To evaluate the effect of age and vestibular deficit on the vestibulo-ocular and associated visual reflexes, rotating chair (VOR), eye tracking test (ETT) and optokinetic (OKN) responses were investigated using comparisons between three populations: young normals, vertiginous elderly patients, and age-matched normal elderly subjects. The gain of ETT and OKN responses were reduced for both elderly populations as compared to young normals, but less so for the vertiginous elderly. VOR gain was more significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…found that vestibulo‐ocular and visuo‐ocular responses were reduced in the elderly, but that in those with vertigo, visuo‐ocular responses were less reduced, possibly as a compensatory mechanism. 4 Intersubject variability in caloric responses was much greater in the elderly. 5 …”
Section: Discussionmentioning
confidence: 99%
“…found that vestibulo‐ocular and visuo‐ocular responses were reduced in the elderly, but that in those with vertigo, visuo‐ocular responses were less reduced, possibly as a compensatory mechanism. 4 Intersubject variability in caloric responses was much greater in the elderly. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Lewis 13 found that infants showed reduced OKN gain compared to adults in either direction. Several studies have reported a decrease in OKN gain [14][15][16][17][18][19][20] and a wider variation of OKN gain at older age, 14 which possibly contribute to balance problems in the elderly. 15 We have investigated changes in OKN related to age in a large group of subjects between infancy and senescence using different stimulus velocities with small field stimulation.…”
mentioning
confidence: 99%
“…Nevertheless, ageing is associated with an increase in the visual contribution, and the elderly therefore seem to rely more on exteroceptive afferent than body afferent [2,6]. Vestibular inputs, which have an important role in postural control [9], display an age-related decrease in excitability [10,11] on account of the lower number of hair cells in the semicircular canals [12,13], the reduction in primary vestibular neurones [13], and the reduction in the utriculus and sacculus macula [14]. Moreover, vestibular omission can be an additional age-related factor [15].…”
Section: Introductionmentioning
confidence: 99%